Enhancement of performance of a hybrid SAC–OCDMA system using dynamic cyclic shift code - Thanaa Hussein, Abd; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlisyah, Ahmad, Prof. Madya Dr.; Juwita, Mohd Nordin (Institute of Physical Optics, 2012)
Link to publisher's homepage at http://www.ifo.lviv.ua/